CT perfusion in predicting the morbidity and prognosis of hypoxic-ischemic encephalopathy after off-pump coronary artery bypass grafting. (3rd June 2017) - Luo, Di; Yip, James; Song, Zhe; Xu, Baolei; Bi, Qi
Abstract: Objective: To investigate the perfusion parameters of computed tomography (CT) in hypoxicischemic encephalopathy (HIE) after off-pump coronary artery bypass grafting (OPCABG), and its potential in predicting the occurrence and prognosis of hypoxic-ischemic encephalopathy. Methods: We selected 830 patients. The patients were grouped into: HIE and no HIE. HIE patients were further divided into two groups: poor prognosis and better prognosis. Results: (1) Patients with HIE, who had a history of stroke and hypertension, showed more severe stenosis on CTA and more perfusion abnormalities compared to non-HIE patients ( p < 0.05). (2) The differences in frontal, temporal, occipital lobe rTTP, and occipital lobe rMTT in patients with or without HIE were statistically significant ( p < 0.05). (3) Logistic regression analysis showed that the difference in occipital lobe rTTP was an independent risk factor for the morbidity in HIE. (4) HIE patients, if they had a history of an abnormal CT, showed poor prognosis ( p < 0.05). Furthermore, in these patients, CT images showed significant differences in right frontal, occipital, basal ganglia rTTP, as well as left temporal, occipital, basal ganglia rTTP, as well as frontal lobe rMTT. (5) Three principal components ( F 1, F 2, F 3) can be used to generalize all indexes. Conclusion: The difference in occipital lobe rTTP on CTA perfusion may be a potential predictor of HIE. Furthermore, abnormal CT and rTTP may be used for predicting the prognosis in HIE patients. Three principal components ( F 1 as a reflection of CBF, F 2 as reflection of TTP, F 3 as a reflection of MTT) can be used to generally describe perfusion parameters.